FIRST CASE TO CONSIDER THAT A CHIMPANZEE MIGHT BE A LEGAL PERSON TO COME BEFORE THE COURT UNDER A PETITION FOR HABEAS CORPUS - CRUZ, Edmundo Lucio da (Revista Brasileira de Direito Animal, 2013)
Opinion of the Court: In favor of: Suica Requested by: Heron Jose de Santana, Luciano Rocha Santana, Antonio Ferreira Leal Filho, Tagore Trajano de Almeida Silva and others Co-plaintiff authority: Thelmo Gavazza, Director of Biodiversity, Environmental and Hydrological Resource Department